Building a Discursive System of Integrating Chinese and Foreign Cultures: Translation Study of Poetry and Ancient Texts in the Diplomatic Interventions of Chinese Leaders - Shiyang, Liu; Yiming, Hao (Sinología hispánica. China Studies Review, 2026)
With the continuous advancement of Chinese diplomacy and the growing ties between China and other countries, new challenges and requirements have been posed for the translation of political texts, particularly the diplomatic interventions of Chinese leaders. Based on the theories of functional equivalence and political equivalence in translation, this study proposes a classification of translation techniques applicable to poems and ancient texts present in diplomatic interventions. It also constructs a Chinese-Spanish parallel corpus of Chinese poems and ancient texts found in the diplomatic interventions of Chinese leaders and analyzes the use of translation techniques such as literal translation, amplification, transposition, explanation, adaptation, and omission, employing content analysis and discourse analysis as the methodology. It is proposed that the translation should be based on the principle of functional equivalence or political equivalence, considering elements such as the recipient, the context, the purpose of the original text, and the translation. From this, appropriate translation techniques should be adopted to facilitate understanding and acceptability by the recipients while simultaneously disseminating Chinese culture, policies, and ideology, with the aim of contributing to the creation and improvement of a Chinese political discourse system that integrates foreign and Chinese cultures in Spanish-speaking countries.